The Impact of Logistics Performance on Trade - Hausman, Warren H.; Lee, Hau L.; Subramanian, Uma (Production and Operations Management, 2013)
This paper studies the impact of logistics performance on global bilateral trade. Taking a supply chain perspective, logistics performance refers to cost, time, and complexity in accomplishing import and export activities. We draw on a data set compiled by the World Bank containing specific quantitative metrics of logistics performance in terms of time, cost, and variability in time. Numerous researchers have shown that logistics performance is statistically significantly related to the volume of bilateral trade. Our research calibrates the impact of specific improvements in logistics performance (time, cost, and reliability) on increased trade. Our findings can spur public and private agencies that have direct or indirect influence over logistics performance to focus attention on altering the most relevant aspects of logistics performance to improve their country's ability to compete in today's global economy. Moreover, as our logistics metrics are directly related to operational performance, countries can use these metrics to target actions to improve logistics and monitor their progress.